Silver nanocube-enhanced far-red/near-infrared fluorescence of conjugated polyelectrolyte for cellular imaging - Gurzadyan, Gagik G. (2013)
We present the study of silver nanocube (Ag NC)-enhanced fluorescence of a cationic conjugated polyelectrolyte (CPE) for far-red/near-infrared fluorescence cell imaging. Layer-by-layer self-assembly of polyelectrolytes on 78 nm Ag NCs is used to control CPE–metal distance and its effect on CPE fluorescence. The highest fluorescence enhancement factor (FEF) is obtained for Ag NCs with two bilayers, corresponding to a CPE–metal spacer thickness of 6 nm. At the optimal excitation wavelength, the FEF is 13.8 with respect to the control silica nanoparticles (NPs). The fluorescent NPs are further used for cellular imaging studies. The CPE-loaded Ag NCs with two bilayers exhibit excellent image contrast, superior to the control of CPE–silica NP at a similar uptake efficiency. The viability test indicates low cytotoxicity of the CPE-loaded Ag NCs, rendering them as promising cell imaging agents.